Advertising Agency Compensation: A Model for Incentive and Control - Calantone, Roger J.; Drury, Donald H. (Management Science, 1979)
This paper describes a theoretical model for incentive and control within the framework of the advertising agency-client relationship. This particular interorganizational relationship has been characterized by frequent disagreements, discontent and resignation of accounts by both sides. For many years simple commission schemes were the rule. Recently many alternative schemes have been instituted but have either had no effect or overly favored one party or the other and thus exacerbated the historical discontent in the industry. The problem is identified through an examination of the major client-agency compensation methods currently in use. The article deals first with the effects and drawbacks of making the simple commission rate method more complex by introducing an increasing number of numerical statements of the variables with which the advertisers and agencies must deal. Then four simple compensation methods—the commission basis, the fixed fee method, time-charges and a results incentive program—are analyzed and compared to introduce an alternative, three-stage approach to compensation. In the first or preliminary stage, the agency proposes to the advertiser a tentative target and a tentative compensation which as been determined by means of an equation which guarantees the agency a normal return. In the second or planning phase, the agency has the option of selecting according to a formula a larger or smaller plan target with a correspondingly larger or smaller compensation payment. In the third or implementation phase, when the agency acutally provides the service negotiated in stage two, it actually receives the corresponding agreed-upon compensation appropriate to its inputs and performance. Thus the model presented provides output performance incentives to both agency and client while providing controls on inputs for both sides. It also explicitly recognizes the planning and negotiation facets of compensation schemes through which the accommodation of each set of organization goals may be achieved.